Daya Tarik Kampung Wisata Tahu Cibuntu Babakan sebagai Destinasi Wisata Baru di Kota Bandung - Siti Nur Fadilah (Universitas Palangka Raya, 2023)
The aim of the researchers to conduct this research is to find out about the history and origins of the Cibuntu Babakan area as a tofu industrial area until now a new destination titled